2007
DOI: 10.3174/ajnr.a0542
|View full text |Cite
|
Sign up to set email alerts
|

Complex-Shaped Platinum Coils for Brain Aneurysms: Higher Packing Density, Improved Biomechanical Stability, and Midterm Angiographic Outcome

Abstract: BACKGROUND AND PURPOSE:Five to 60% of coiled brain aneurysms recanalize, generally because of coil compaction. In vitro exclusive use of complex-shaped coils allows better packing of the aneurysmal sac and the neck as compared with helical coils. We report a single-center, prospective study using complex coils. Safety, packing density, and recanalization rate were evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 26 publications
1
63
0
Order By: Relevance
“…Packing attenuation, the volume ratio of implanted coils to the volume of the aneurysm, was calculated as previously described. 9 We calculated coil volume for each aneurysm, assuming that the coil was a solid cylinder by using the primary coil diameter given in the manufacturer's specifications.…”
Section: Angiographic and Endovascular Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Packing attenuation, the volume ratio of implanted coils to the volume of the aneurysm, was calculated as previously described. 9 We calculated coil volume for each aneurysm, assuming that the coil was a solid cylinder by using the primary coil diameter given in the manufacturer's specifications.…”
Section: Angiographic and Endovascular Proceduresmentioning
confidence: 99%
“…In addition, aneurysm recanalization is observed in 20%-40% of cases due to coil compaction, migration of coils into the aneurysm thrombus, or aneurysm growth. [7][8][9][10] Introduction of stents designed as an adjunct tool for coiling has been shown, in the short-term, to be of beneficial value. [11][12][13][14][15] However, a variety of devices, different in their design and coating, was used with a high periprocedural mortality and morbidity.…”
mentioning
confidence: 99%
“…4) However, initial complete occlusion and high embolization rates are important factors that significantly decrease the recurrence rate after treatment. 5,6) Stable framing may lead to subsequent stable filling/finishing, playing an important role in achieving a high embolization rate. Several studies reported that complex coils showed higher embolization and lower recanalization rates compared with helical coils.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where microcatheter movement is restricted, it is important to understand the role of the coil's shape memory and the stiffness of the coil on coil distribution. Moreover, various types of coils [12][13][14][15] have been developed for the treatment of unfavorable aneurysm configurations. However, a consensus has not been established regarding the most effective coil type for the coil embolization of wide-necked and bilobulated aneurysms with stent assistance, as basic research is lacking.…”
Section: Introductionmentioning
confidence: 99%